The organizational design of offshoring - Marcus Møller Larsen (Copenhagen Business School (CBS), 2013)
Offshoring can be defined as the relocation of organizational tasks and services to foreign locations. Increasingly, firms experience that unforeseen costs and difficulties of managing offshoring undercut anticipated benefits; that unexpected challenges of offshoring jeopardize and eventually undermine initial objectives. Guided by the research question—what are the organizational consequences of offshoring?—the purpose of this thesis is to investigate why some firms fail when offshoring and other do not. The thesis consists of four research papers using various datasets and methodologies that investigate offshoring in an organizational context. The first paper investigates how the complexity of offshoring leads to `hidden costs' of implementing offshoring activities. The second paper looks at how these hidden reconfiguration costs influence the process performance of the offshored activity and how this relationship is moderated by the modularity of that activity. The third paper investigates the effect of the organizational reconfiguration of offshoring on firms' strategies. The final paper studies different strategies of adaptation in offshoring. Taken together, this thesis argues that whether firms relocate activities with the purpose of accessing resources or as a response to political pressures, the process of offshoring presents firms with the challenge of coordinating and integrating offshoring activities in a global organization. The complexities and uncertainties of an organization consisting of a number of offshored activities (in contrast to an organization with only co-located activities) require firms to invest additional resources in coordination mechanisms so that an efficient reintegration can be achieved.
hdl:10398/8669
Keywords: 650